DYNAMICS OF VITAL VALUES OF ADOLESCENTS AND A PROBLEM OF CORRUPTION IN POST-SOVIET RUSSIA - Pyotr N. Kondrashov (Obrazovanie i Nauka, 2016)
The purpose of the article is to show immanent interrelation between structure of terminal and tool vital values of adolescents of the Post-Soviet period and predisposition to perpetrate of corruption actions. Methods. The methods involve philosophical analysis, supervision, questioning under the formalized questionnaire, conversation, and longitudinal research. The program of research includes the questions connected with different aspects, factors and motives of valuable orientations of adolescents.Results. Results of longitudinal research (1998–2014) of dynamics of vital values of adolescents are presented. It is established that the structure of adolescent’s axio-sphere has radically changed for the studied period. In 1998, the most important life values were money, material well-being; in contrast to 2014 when the values are good health and love. Thus, there is a reorientation of adolescents from mercantile values to spiritual values. On the other hand, the system of instrumental values changes. In 90-s, the main means of achieving life goals were money, violence and helping of other people; it is in contrast to 2014 when teenagers are guided more by their own strength.Scientific novelty. It is for the first time shown that feature of vital values of modern city teenagers is inability of long expectation of realization of the vital purposes. It is burdened also by the fact that many vital values (education, health, love, friendship) turn into exchange values (costs) in modern capitalist society. Therefore teenagers prefer to use money as means of instant achievement of the purposes. These factors form real predisposition of adolescents to perpetrate corruption actions.Practical significance. The presented investigation can be interesting to parents, tutors of preschool institutions, teachers of schools, experts in the field of psychology, sociologists, lawyers, and law enforcement officers.